Tropical Medicine and Health - Hashizume, Masahiro
Tropical Medicine and Health is an open access, peer-reviewed journal that publishes original research and reviews on all aspects of tropical medicine and global health. The journal welcomes clinical, epidemiological, laboratory and policy research. Key topics include: • Viral, bacterial and parasitic infectious diseases • Vectors • Poisonous and venomous organisms • Noncommunicable diseases • Epidemiology and population health • Drug, vaccine and diagnostic tool development • Traveller’s health • Health systems, services and policy • Other health issues related to the tropics The journal accepts original research, reviews, short reports, case reports and letters to the editor.